2013
DOI: 10.1016/j.molcel.2013.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Consequences of Deleting Any Single Gene

Abstract: Summary Loss or duplication of chromosome segments can lead to further genomic changes associated with cancer. However, it is not known if only a select subset of genes is responsible for driving further changes. To determine if perturbation of any given gene in a genome suffices to drive subsequent genetic changes, we analyzed the yeast knockout collection for secondary mutations of functional consequence. Unlike wild type, most gene knockout strains were found to have one additional mutant gene affecting nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
198
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(208 citation statements)
references
References 49 publications
9
198
1
Order By: Relevance
“…Another possible explanation for the viability of the ⌬mhb1 mutant is that the deletion resulted in a genomic imbalance that was compensated for by secondary mutations elsewhere in a genome. In fact, it was shown recently that most gene knockout strains of S. cerevisiae acquired additional mutations selected to counteract the effect(s) of the original genetic defect (86). To explore this possibility, we tried to obtain independent clones lacking the YlMHB1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for the viability of the ⌬mhb1 mutant is that the deletion resulted in a genomic imbalance that was compensated for by secondary mutations elsewhere in a genome. In fact, it was shown recently that most gene knockout strains of S. cerevisiae acquired additional mutations selected to counteract the effect(s) of the original genetic defect (86). To explore this possibility, we tried to obtain independent clones lacking the YlMHB1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although the Tspo −/− mice were viable and physiologically functional, Banati et al reported a severe bioenergetic deficit in glial cells isolated from these Tspo −/− animals (19). Although adaptive responses in genetically engineered organisms have been reported (31,32), systematic exploration of this question has only just begun to be explored in genetically characterized organisms such as yeast, indicating that genetic adaptation to targeted gene deletion is highly reproducible and widespread (33). Understanding the commonalities and differences between the Tspo-deletion mouse models may provide insight into such processes in higher metazoan genetic models such as mice.…”
Section: Discussionmentioning
confidence: 99%
“…This may account for the copy number change of Vmn2r111 and Vmn2r112 herein. Engineered copy number change or mutation of single genes has previously been found to induce copy number change of unrelated genes and mutations in secondary effect genes leading to impaired expression [40]. For Vmn2r112 there was moderate and markedly decrease in expression in Glo1(+/+) Gt(..)1Lex and Glo1(+/+) Gt(..)2Lex mutant mice, respectively.…”
Section: Discussionmentioning
confidence: 97%